1979
DOI: 10.1128/iai.25.3.786-791.1979
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria toxin-binding glycoproteins on hamster cells: candidates for diphtheria toxin receptors

Abstract: Diphtheria toxin-binding glycoproteins of high molecular weight (>100,000) were identified on the surface of lymph node and thymus cells from hamsters, a diphtheria toxin-sensi Jve species. These diphtheria toxin-binding glycoproteins also interacted with CRM197 protein, which possesses toxin-blocking activity, but not with diphtheria toxoid, fragment A of diphtheria toxin, or cholera toxin, all of which lack toxin-blocking activity. These observations are consistent with the hypothesis that the detected dipht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…42:1809, 1983; manuscript in preparation) have been identified and characterized. It has been suggested that these DT-binding cell surface glycoproteins are likely candidates for the DT receptor (27)(28)(29)(30). These glycoproteins have a high molecular weight (ca.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…42:1809, 1983; manuscript in preparation) have been identified and characterized. It has been suggested that these DT-binding cell surface glycoproteins are likely candidates for the DT receptor (27)(28)(29)(30). These glycoproteins have a high molecular weight (ca.…”
mentioning
confidence: 99%
“…These glycoproteins have a high molecular weight (ca. 150,000 and 70,000) and show anomalous behavior on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, indicating the presence of a significant degree of carbohydrate (27). The binding of DT to these cell surface glycoproteins has been shown to be specific for the B fragment of the toxin (27,28,30).…”
mentioning
confidence: 99%
See 3 more Smart Citations